2012
DOI: 10.5483/bmbrep.2012.45.5.293
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and immunohistochemical localization of a mitogen-activated protein kinase, Accp38b, from Apis cerana cerana

Abstract: The p38 mitogen-activated protein kinase (MAPK) is involved in various processes, including stress responses, development, and differentiation. However, little information on p38 MAPK in insects is available. In this study, a p38 MAPK gene, Accp38b, was isolated from Apis cerana cerana and characterized. The quantitative real-time PCR (Q-PCR) analysis revealed that Accp38b was induced by multiple stressors. Notably, the expression of Accp38b was relatively higher in the pupae phase than in other developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
(35 reference statements)
2
11
0
Order By: Relevance
“…Tissue-specific expression analysis showed that AccMKK6 is expressed in various tissues but is most highly expressed in the thorax and epidermis. Similarly, the highest expression of Accp38b has been detected in the thorax [34]. The epidermis acts as the exoskeleton, conferring physical stability, and participates in the responses to various environmental stresses [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue-specific expression analysis showed that AccMKK6 is expressed in various tissues but is most highly expressed in the thorax and epidermis. Similarly, the highest expression of Accp38b has been detected in the thorax [34]. The epidermis acts as the exoskeleton, conferring physical stability, and participates in the responses to various environmental stresses [41].…”
Section: Discussionmentioning
confidence: 99%
“…The typical MAPK member Accp38b (GenBank accession no. GU321334) was isolated as previously described [34] and ligated into the pGBKT7 vector. The ORFs of AccMKK6 and Acckayak were cloned and fused to the pGADT7 vector.…”
Section: Methodsmentioning
confidence: 99%
“…). However, the higher or lower expression level of p38 is different in different animals (Livak & Schmittgen ; Hansen & Jørgensen ; Cai, Huang, Wei, Huang, Ye, Fu & Qin ; Zhang, Meng, Li, Kang, Guo & Xu ). This experiment found that the expression of Es‐p38 in muscle is significantly higher than other tissues, and it is also higher in hepatopancreas, intestine, testis, ovary, accessory gonad, but lower in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…AccMGST2 expression was the highest in the head of A. cerana cerana , followed by the muscle (Figure 4). The tissue expression characteristics of AccMGST2 were similar to those of the Accp38b gene from A. cerana cerana (Zhang et al, 2012), and AccMGST2 and Accp38b may have synergistic effects. Additionally, the tissue‐specific expression of one gene is related to its biological function.…”
Section: Discussionmentioning
confidence: 59%